ECOLOGICAL ANALYSIS OF UNDERSTORY VEGETATION AROUND ENDANGERED ORCHID PENCIL (Vanda hookeriana Rchb.) FROM LAKE DUSUN BESAR NATURE RESERVE BENGKULU - Roziaty, Efri (Proceeding of International Congress, 2014)
The research on Ecological Analysis Of Understory Vegetation Around Endangered Orchid Pencil (VandaHookeriana Rchb.) From Danau Dusun Besar (DDS) Nature Reserve Bengkulu held on February to December2013. The research is located around endangered Pencil orchid in DDS Bengkulu Province. Pencilorchid is an endangered orchid in the world. Itâs an endemic orchid from DDS Bengkulu Province. Theresearch used purpossive sampling techniques in site selection and using 2 m x 2 m = 4 m2 plot for sampling.The highest Important Value Index (INP) value is Imperata sp. (Graminae) 78.60 %. Some ecologicalfactors which influenced the vegetation such as temperature, humidity, sunlight penetration and the pHof the water. The researcher stated that the assessment needs to be done about the ecological aspects oforchid pencil in their natural habitat.Key words : Danau Dusun Besar Bengkulu, understory vegetation, endemic orchid.